BIBB Establishment Panel on Training and Competence Development : the longitudinal data set - Anett Friedrich [Verfasser]; Lukowski, Felix [Verfasser] (My University, 2023)
“The BIBB Establishment Panel on Qualification and Competence Deve lopment is the second largest annual panel survey of firms in Germany. In this article, we present the harmonised longitudinal data set from the first wave in 2011 to the 2019 wave, comprising 32,135 observations from 15,918 firms. We present information on the sample, study design and data collection and describe the characteristics of the survey. We explain the structure of the long data set designed for facilitating panel analyses. The data provides comprehensive information on firms’ human resources management, particularly in respect of vocational education and training and continuing training. Since 2016, the survey has also followed technological change and the training and employment of refugees. We present previous findings using the data, based on which we give an outline of the survey’s potential for future research. The Research Data Centre at the Federal Institute for Vocational Education and Training provides and regularly updates the data set.“ (authors‘ abstract; BIBB-Doku)

“Das BIBB-Betriebspanel zur Qualifizierung und Kompetenzentwicklung ist die zweitgrößte jährliche Panelbefragung von Betrieben in Deutschland. In diesem Beitrag stellen wir den harmonisierten Längsschnittdatensatz von der ersten Welle im Jahr 2011 bis zur Welle 2019 vor, der 32.135 Beobachtungen von 15.918 Betrieben umfasst. Wir informieren über die Stichprobe, das Studiendesign und die Datenerhebung sowie die Merkmale der Erhebung. Weiterhin erläutern wir die Struktur des long Datensatzes, der für Panelanalysen konzipiert ist. Die Daten liefern umfassende Informationen zum Personalmanagement der Unternehmen, insbesondere zu beruflicher Bildung und Weiterbildung. Seit 2016 verfolgt die Erhebung auch den technologischen Wandel sowie die Ausbildung und Beschäftigung von Geflüchteten. Wir stellen bisherige Ergebnisse anhand der Daten vor und skizzieren auf dieser Basis das Potenzial der Erhebung für die zukünftige Forschung. Das Forschungsdatenzentrum am Bundesinstitut für Berufsbildung stellt den Datensatz zur Verfügung und aktualisiert ihn regelmäßig.“ (Autorenreferat; BIBB-Doku)
Keywords: T 3 Forschungsmethoden; 370; Betriebspanel; Kompetenzentwicklung; Qualifizierung; Datengewinnung; Forschungsdatenzentrum; 2011-2019